Lia Saniah Analisis Kemampuan Disposisi Matematis melalui Model Pembelajaran Probing Prompting pada Siswa Sekolah Menengah - Lia Saniah; Agus Dede Anggiana (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2022)
This study aims to examine whether the achievement of the mathematical disposition of students who receive learning using the Probing-Prompting learning model is better than students who receive conventional learning. The method used in this research is quasi-experimental. The research sample consisted of two classes. Obtained class X MM 1 as the experimental class who received the Probing Prompting learning model and class X MM 2 as the control class who received the Problem Based Learning learning model. The instrument used in this study was a liqueur scale questionnaire. The collected data was then processed using IBM SPSS 23.0 for Windows software. The results showed that the mathematical disposition of students who received learning using the Probing Prompting model was better than students who received the Problem Based Learning learning model